Behavior response of blue swimming crab (Portunus pelagicus) to the different entrance gates of collapsible pot - Henita Aditya; Wazir Mawardi; Mochammad Riyanto (Journal Omni-Akuatika, 2020)
The behavior of blue swimming crab (BSC) (Portunus pelagicus) to the collapsible pot is observed to redesign the entrance of the pot with high effectiveness. The purpose of this study is to analyze the behavior response of BSC to the entrance gate of the collapsible pot by laboratory experiments. The behavior response of the BSC (100-150 mm of carapace width (CW), n= 15) to the two angles of the entrance gate, that were 200 as control and 400 as a modification of the collapsible pot. The movement and speed of the crab to the entrance gate were observed by using CCTV Camera. The results showed that the percentage of crabs failed to find the entrance was higher than crab that be successful to enter the pot. The crab that failed to find the entrance was 43% for control and 52% for modification pot, while the crab that be successful to enter was 24% for control pot and 19% for modification pot. There were five movement patterns of crab to the pot i.e. straight to entrance, side to entrance, side to side, entrance to side, and straight to side. The average speed of entrance crab was 127.89 ± 46.48 for control, and 88.45 ± 5.74 for modification pot. Keywords: behavior, response, blue swimming crab, collapsible pot, Portunus pelagicus